Reference Values for Handgrip Strength in the Basque Country Elderly Population - Xabier Río; Arkaitz Larrinaga-Undabarrena; Aitor Coca; Myriam Guerra-Balic (Biology, 2020)
Strength training is currently the most recommended primary therapeutic strategy to prevent and reverse the decline of muscle mass, strength, and functional deterioration associated with age. The aim is to provide reference values of handgrip strength (HGS) in the Basque Country population and compare the values with other populations. A total of 1869 subjects from the health-promoting programme for adults and older adults run by the Bilbao City Council were assessed using HGS with a digital dynamometer and anthropometric data measured by Tanita to obtain the mean values according to age distribution. From the 1869 subjects, 87.5% were women and 12.5% men. The HGS was higher among men than women, 32.4 ± 6.6 versus 20.1 ± 4.7 kg, respectively, p < 0.001 at all ages. Weak HGS cut-off points by age groups ranged from 31.0 to 23.8 and from 18.9 to 12.4 in men and women, respectively. The sample data were compared (d, t, and α) with those of other populations in all age groups (group > 60 years at 95% df, p < 0.05). A health-promoting programme appears to be effective in the general population in obtaining better values in the HGS test as age increases.